Phylogenetic Analysis of Coral Fish Familia Chaetodontidae Based on Chytocrome Oxydase I (Coi) Markings in the Core Zone and Limited Use Zone of Taman Pulau Kecil, Padang City, West Sumatra in the Context of Environmental Conservation - Rhavy Ferdyan; Ramadhan Sumarmin; Abdul Razak (Science and Environmental Journal for Postgraduate, 2021)
This article aims to explain the coral reef fish relationship of the Chaetodontidae family based on the Chytocrome Oxydase Imarkers (COI). This research uses a qualitative descriptive approach. This qualitative descriptive study aims to determine the sequence of nucleotide bases offish Chaetodontidae in the COI area through the reading of sequences which are then used as material for making phylogenetic trees. Analyzes were performed using MEGA 10 software. The analysis was based on previous research, it was obtained the types of reef fish that inhabit the waters of the Taman Pulau Kecil of the city of Padang. The species are scattered in two zones, namely the core zone and the limited use zone in the Taman Pulau Kecil area of ​​Padang city. From the results of the analysis using MEGA 10 software, it was obtained that the level of kinship between the species tested was very close, including the species Chaetodon trifasciatus, Chaetodon vagabandus, Chaetodon triangulum, and Chaetodon lineolatus. The genetic mean distance of all species was 0.02. In general, the species relatedness found are several species found in the same location with almost the same morphology and food. By obtaining the results of the phylogenetic analysis which directly describes the level of the kinship of the Chaetodontidae group, these results can be used as the material in the development of molecular ecology and a reference in environmental conservation.